2013
DOI: 10.1259/bjr.20120278
|View full text |Cite
|
Sign up to set email alerts
|

The value of image-guided intensity-modulated radiotherapy in challenging clinical settings

Abstract: IG-IMRT can offer improved outcomes in less common clinical situations, where conventional techniques would provide suboptimal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Approximately 440 new cases are treated per annum across our 2 TomoTherapy units, with about 45% prostate cancer, 24% head and neck cancer (HNC), 8% central nervous system (CNS) tumours and 23% other cases [7,15]. All patients are imaged daily.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 440 new cases are treated per annum across our 2 TomoTherapy units, with about 45% prostate cancer, 24% head and neck cancer (HNC), 8% central nervous system (CNS) tumours and 23% other cases [7,15]. All patients are imaged daily.…”
Section: Methodsmentioning
confidence: 99%
“…Technical developments such as intensitymodulated radiotherapy (IMRT) have facilitated dose escalation and toxicity reduction by more effectively conforming the high dose volume to the shape of the target [1][2][3][4][5][6][7]. This is particularly true of tumour sites with complex irregular shapes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these technological advances, radiotherapy has undergone a major transformation over the past decade. Recent results have also shown that new techniques and dose escalation have increased the potential of disease-free survival [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%